2021
DOI: 10.3389/fmicb.2020.622368
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analyses of Repeat-Induced Point Mutations in the Ascomycota

Abstract: The Repeat-Induced Point (RIP) mutation pathway is a fungus-specific genome defense mechanism that mitigates the deleterious consequences of repeated genomic regions and transposable elements (TEs). RIP mutates targeted sequences by introducing cytosine to thymine transitions. We investigated the genome-wide occurrence and extent of RIP with a sliding-window approach. Using genome-wide RIP data and two sets of control groups, the association between RIP, TEs, and GC content were contrasted in organisms capable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 125 publications
5
33
0
Order By: Relevance
“…S5b and ). As previously reported in other fungi, the Hi-C interaction frequency indicated the approximate location of centromeres [96–99]. In C. fulvum , centromeres are putatively located proximal to chromosome ends (Fig.…”
Section: Resultssupporting
confidence: 79%
“…S5b and ). As previously reported in other fungi, the Hi-C interaction frequency indicated the approximate location of centromeres [96–99]. In C. fulvum , centromeres are putatively located proximal to chromosome ends (Fig.…”
Section: Resultssupporting
confidence: 79%
“…The investigation on the genome-wide occurrence of RIP in Monilinia showed that all the three strains showed RIP hallmarks, and that these are likely to be mediated by the RID and DIM-2-mediated DNA methylation pathways ( Gladyshev, 2017 ), as suggested by detection of key genes of these pathways: the two methyltransferases (RID, DIM-2) and the DIM-2-associated cofactors. The only exception was the cofactor DIM-7, which was absent in the Monilinia genomes, in line with what was recently reported for B. cinerea , S. sclerotiorum and several other Ascomycetes ( van Wyk et al, 2021 ). Slight differences among the three genomes were observed in terms of the extent of this phenomenon.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, there may be other contributing factors to the observed mutational differences between HLT and LLT, such as dysfunction in other DNA repair pathways, loss of methyl transferases, and differences in chromatin structure (Steenwyk, Opulente, et al 2019; Möller et al 2021). For example, previous studies have identified the loss of genes involved in the repeat-induced point (RIP) mutation pathway in powdery mildews (Spanu et al 2010; van Wyk et al 2021). Loss of genes in the RIP pathway in HLT could contribute to the elevated mutation rates we observed relative to LLT.…”
Section: Discussionmentioning
confidence: 99%